2015
DOI: 10.1590/s1413-70542015000300007
|View full text |Cite
|
Sign up to set email alerts
|

Licury Cake in Lamb Feed: Characteristics of Carcass and Non-Carcass Components

Abstract: The use of alternative foods, such as agroindustrial residues, for animal feeding aims to reduce production costs and increase animal productivity. Therefore, the objective of this study was to evaluate the effect of different levels of licury cake added to the diet of non-standardbred lambs (NSB). The study involved 20 male castrated NSB lambs, with an average age of 120±5 days and initial and final average weights of 25±2 kg and 34±2 kg, respectively; the lambs were kept in a feedlot and distributed in a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, the FT was lower in our treatments, ranging from 1.41 to 0.81 mm. On the other hand, Santos et al [ 1 ] reported a quadratic effect (p<0.05) on animal performance without changes in the FT of longissimus muscles when lambs were fed licuri cake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the FT was lower in our treatments, ranging from 1.41 to 0.81 mm. On the other hand, Santos et al [ 1 ] reported a quadratic effect (p<0.05) on animal performance without changes in the FT of longissimus muscles when lambs were fed licuri cake.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of 24% licuri cake in diets fed to lambs has led to a 39% reduction in intake and a decreased weight gain and average daily gain (ADG) [2]. On the other hand, a 17% inclusion of licuri has been reported to improve feed conversion and to increase ADG [3], and no changes in the dry matter intake (DMI) of lambs was observed with 16% inclusion of licuri cake [1]. In addition, the fatty acid profile of licuri oil is different from traditional oil sources; it is highly saturated, with high percentages of medium chain fatty acids (MCFA), mainly lauric and myristic acids [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a decrease in lamb performance due to decreased dry matter intake was observed [240]. The lambs fed with 16% licuri cake had no changes in the dry matter intake [241]. Nonetheless, the addition of 24% licuri cake in the feed of lambs resulted in a 39% reduction in intake, decrease in weight gain, and average daily gain [242].…”
Section: Macaúba Kernelmentioning
confidence: 99%
“…Additionally, the neutral detergent fiber in LC is as effective as that of hay (Daza et al, 2021). Researchers who replaced soybean meal (the main dietary source of protein) with LC in the diet of sheep described a decrease in nutrient intake and digestibility, performance, and carcass traits (Santos et al, 2015;Costa et al, 2016). More recently, studies have suggested the possibility of including up to 100 g/kg LC in high-grain diets for steers and goat kids (Silva et al, 2020;Silva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%